The “Zofia’s Text” of Iosif Brodsky: The Start (1961–1962) - Бараш, Ольга (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The paper discusses two pieces of poetry from the early period of Iosif Brodsky’s creative work (early 1960s): the long poem Zofia and the 16-line verse “Leti otsiuda, belyi motyljok…” [En. “Fly away from here, white moth…”], dedicated to the addressee referred to in “Zofia”. The presumption is that Brodskii’s verses dedicated or referring to his Polish friend Zofia Kapuścinska (Z. K.) form a kind of hypertext with a single set of images, motifs, and subtexts, which, according to Vladimir Toporov’s terminology, may be defined as the “Zofia’s Text”. The paper presents some facts from the poet’s biography that gave rise to the “Zofia’s Text” and provides a comparative analysis of the two mentioned works. Guided by Vladimir Toporov’s methodological principles used in his study of the “Liza’s Text” in Russian literature, the author points out the conceptual features of “Leti otsiuda, belyi motyljok…” and shows how all of them were later reproduced and elaborated in “Zofia”. Without making it her aim to undertake a comprehensive analysis of the texts, the author confines herself to considering some lexical and lexical-grammatical means, interpreting some images and motifs, and identifying some sense-forming subtexts that can be taken as differential features characteristic of the assumed hypertext.